Kontribusi Pesantren dalam Penguatan Visi Pendidikan Bangsa - Achmad Reza Hutama Al Faruqi; Rif’at Husnul Ma’afi; M. Aldian Munandar (INTEGRATIA: Journal of Education, Human Development, and Community Engagement, 2023)
This article aims to explain the role of Islamic boarding schools as strengthening the nation's educational vision. Islamic boarding schools as educational institutions train and form students to have noble values that are not only oriented towards religion, but also science. Many people think that Islamic boarding schools are shabby, innocent and a cloud of knowledge. Through the library-descriptive method, this paper emphasizes that the realization of intelligent and competitive Indonesian people (insan kamil) can only be achieved through Islamic boarding school educational institutions. The results of this research confirm that Islamic boarding schools not only teach intelligent people intellectually but also spiritually. This then became the ideal of the Indonesian nation, producing intelligent and competitive Indonesian people (insan kamil).